(untitled) (Journal of Science and Engineering, 2026)
The damping ratio is a critical parameter in vibration analysis, representing the energy dissipation capacity of structural components. Accurate assessment of damping behaviour is essential for predicting the dynamic response of structures such as machinery, buildings, and bridges. This study aims to determine the damping ratio of a SDOF system using the logarithmic decrement method. Physical SDOF system were fabricated from mild steel sections measuring 20 mm in width and 3 mm in thickness, with a 1 kg lumped mass attached at the free end to simulate dynamic loading. Free vibration tests were conducted, and displacement-time data were measured using a VLX50LOX sensor. The damping ratio were calculated by applying the logarithmic decrement formula to the decay of successive vibration amplitudes. Initially numerical computation was conducted by setting the time periods between 0.5 and 1.5 seconds by varying length of SDOF system. The Rayleigh method, Finite Element Method (FEM) and the lumped mass concept were used to calculate corresponding SDOF system length. Means of the sum of lengths calculated at each time period were applied to the analysis of SDOF system using ETABS application software. The preparation of physical specimens was based on these numerical findings, and free vibration experiments were carried out on fabricated specimens. The displacement vs time was measured by a VLX50LOX sensor, and then damping ratio with logarithmic decrement method was determined. The damping ratios obtained for the SDOF specimens were from 0.0042 to 0.0055. This setup can be used as an experimental apparatus for studying a single-degree-of-freedom (SDOF) system in the laboratory.